2016
DOI: 10.1007/s00464-016-5074-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3D in the training of basic laparoscopic skills and its transferability to 2D environment: a prospective randomized controlled trial

Abstract: The 3D environment helped shorten the training time of basic laparoscopic skills to novices. However, the novices trained in the 3D environment failed to transfer their skills to the 2D environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…We also showed that the use of a 2D monitor impaired the performance of trainees after training using 3D indicated by a longer operative time due to longer path lengths and more frequent errors. Saseem et al [ 14 ] reported similar findings, especially in complicated tasks. Our results showed that all scores for performance of task 1 (simple task) (median operative time, path length, and technical errors) in the 3D start group did not differ significantly between just before and after switching to a 2D monitor.…”
Section: Discussionmentioning
confidence: 60%
“…We also showed that the use of a 2D monitor impaired the performance of trainees after training using 3D indicated by a longer operative time due to longer path lengths and more frequent errors. Saseem et al [ 14 ] reported similar findings, especially in complicated tasks. Our results showed that all scores for performance of task 1 (simple task) (median operative time, path length, and technical errors) in the 3D start group did not differ significantly between just before and after switching to a 2D monitor.…”
Section: Discussionmentioning
confidence: 60%
“…auf den GOALS-Score zu ermitteln (wie z. B. Mentoring, Video-Tutorials, 3-D-vs. 2-D-Umgebung), ist die Notwendigkeit einer größeren Fallzahl durchaus zu erwarten [34,35]. Dennoch konnte im Rahmen dieser Studie ein signifikanter Unterschied in der Präzision der MIC anhand der gewählten Fallzahl nachgewiesen werden.…”
Section: Diskussionunclassified
“…Evidence suggests that superior performance during training in simulated laparoscopic tasks (i.e. faster completion times and fewer errors) can be achieved when novices use a 3D viewing mode rather than a 2D display or viewing mode [6][7][8][9]. However, several studies identified that the superior skill acquisition associated with training in 3D was not reflected in subsequent performance during testing in 2D [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…faster completion times and fewer errors) can be achieved when novices use a 3D viewing mode rather than a 2D display or viewing mode [6][7][8][9]. However, several studies identified that the superior skill acquisition associated with training in 3D was not reflected in subsequent performance during testing in 2D [7,[10][11][12]. Further, those trained in 2D performed at a superior level when subsequently tested in 3D [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation